Konstruksi Pendidikan Moral secara Holistik; Pendekatan Baru Pengembangan Pendidikan Agama Islam - Moh. Solehuddin; Siswoyo Siswoyo (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2019)
The developing of Islamic education must be adjusted to the development of education system. One of the ways is to offer a new paradigm i.e. the paradigm of holistic education. It is important to wholly observe the dynamic of education. Partial point of view is now becoming obstacles and problems of education in these days. Education system which is developed at this present is just more dominantly set for students’ preparation to enter higher educational institutions, not to expand the potentials of each individual student. In the context of Islamic education development, the system of holistic education is relevant to be developed because it is able to frame the learners’ pre-life, the education which substantially contain universal values in order the management can be run well with good management and with the right way so that the output of education will have the holistic capability, not partial.